Indirect methods of determination of maximum oxygen consumption - Leonid Serhiyenko (Kharkiv State Academy of Physical Culture, 2015)
Purpose: to describe the methodology of indirect methods of estimation of maximum oxygen consumption. Material and Methods: the work dealt with a method of theoretical analysis and generalization, bibliographical method of search and use of scientific information, systemic analysis. Results: in classification of indirect methods of determination of VO2max there are five groups: method of inquest, tests based on the estimation of functional activity, tests of moderate physical activity, racing tests (consist of three groups of differential tests), tests whined mechanical examples (step tests and veloergometer tests). Conclusion: methodological peculiarities are considered: using of indirect methods of maximum oxygen consumption.